1951
DOI: 10.1039/jr9510001230
|View full text |Cite
|
Sign up to set email alerts
|

274. The thermal decomposition of carbonyl sulphide

Abstract: The equilibrium conditions of the two decomposition reactions of carbonyl sulphide have been further investigated. The reaction leading to carbon dioxide is shown to be peculiarly susceptible to the nature of the vessel wall, and the rate of the reaction has been measured under various conditions. A method has been devised for measuring the rate of the fast reaction leading to carbon mdnoxide, and a number of velocity values have been obtained. The disproportionation of carbon monoxide, considered as a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The available experimental data for thermal conversion of OCS are derived under pyrolysis or oxidation conditions. Data for thermal conversion of OCS in an inert atmosphere (pyrolysis), reported from batch reactors , flow reactors , and shock tubes , were not considered for model validation in the present work. The results are consistent with the reaction sequence, OCS +M CO +S+M OCS +S CO +normalS2 and the rate constant for (R1), derived from the batch reactor (823–873 K) and shock tube work (1500–3230 K), is mostly in agreement within a factor of two (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The available experimental data for thermal conversion of OCS are derived under pyrolysis or oxidation conditions. Data for thermal conversion of OCS in an inert atmosphere (pyrolysis), reported from batch reactors , flow reactors , and shock tubes , were not considered for model validation in the present work. The results are consistent with the reaction sequence, OCS +M CO +S+M OCS +S CO +normalS2 and the rate constant for (R1), derived from the batch reactor (823–873 K) and shock tube work (1500–3230 K), is mostly in agreement within a factor of two (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arrhenius plot for the reaction OCS + M CO + S + M. Experimental results (symbols) from Partington and Neville , Hay and Belford , Schecker and Wagner , Woiki and Roth , Oya et al , and Murakami et al . The solid line denotes the recommendation of Oya et al, which is the preferred value in the present model.…”
Section: Detailed Kinetic Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…Later it was shown by Stock et al (1924) that the CO, reaction is much faster than the CO reaction; reaction 4 was appreciable even at room temperature, whereas reaction 2 began to be measurable only at 400°C. The equilibrium conditions of the two decomposition reactions of COS (reactions 2 and 4) have been investigated by Partington and Neville (1951). It was found that at 450"C, 25% of added CO suppressed the CO reaction and made it possible to study the CO, reaction separately.…”
Section: Cosmentioning
confidence: 99%